MODEL PEMBELAJARAN KOPERATIF DI BAWAH TEKANAN UNTUK MENINGKATKAN HASIL PERKULIAHAN DALAM MATA KULIAH PEMOGRAMAN - Efron Manik (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nom- mensen, 2019)
Job vacancies often include conditions for being able to work in teams and being able to work under pressure for prospective workers. So the learning model, for the last year students who work according to market demand in the workforce, needs to be introduced. The purpose of this study is to create a cooperative learning model under pressure. The steps of the Cooperative Learning Model Under Pressure are (1) explaining learning objectives, (2) explaining apperception and ways of assessment at the end of learning, (3) forming heterogeneous groups, (4) group discussions with peer tutors by press, (5) ) evaluation with pressure and appreciation, and (6) summarizing. The average value of students for Programming courses taught with the cooperative learning model under pressure is significantly better than that taught in the cooperative learning model without under pressure.